Luxury Brands: Awareness and image and its influence on loyalty and engagement - Gallart-Camahort, Valentín; de la Oliva-Ramos, Eugenio; Fernández-Durán, Laura (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This work is based on the concept of Brand Equity in the luxury sector. It analyzes the relationships between Awareness, Image and Loyaty, including Engagement in its relationship with commented variables. A theoretical model was specified and tested by Confirmatory Factor Analysis. Hypothesis have been tested running a structural equations model. Each hypothesis has resulted to be significant. The model had a good fit to the data. The conclusions obtained from the analysis of the data allow us to describe the effects that occur between the variables, being important for their management so that managers of the luxury companies can increase the value of their brands.